KOMITMEN PROFESI DAN PENGARUHNYA TERHADAP KOMPETENSI PROFESIONAL GURU PADA MADRASAH TSANAWIYAH DI KOTA MAKASSAR - Naro, Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2017)
Teachers are key to improving the quality of education, they are at the central point of any educational reform effort. In order to become a professional person, teachers must meet the qualifications and competency standards of educators. The approach used in this study is a multidisciplinary approach that is: religious approach, juridical / normative, management, and sociological. This research was conducted in Makassar City of South Sulawesi Province. The place of research is in all Madrasah Tsanawiyah within the Ministry of Religious Affairs of Makassar City. The object population (target) of this research is all teachers of Madrasah Tsanawiyah in Makassar City consisting of 2 State Islamic Madrasah Tsanawiyah and 32 Private Madrasah Tsanawiyah. The teacher population of 34 Madrasah Tsanawiyah in Makassar City is 729 people. Research Results Shows that the professionalism of Madrasah Tsanawiyah teachers in terms of; 1) Mastery of materials, structures, concepts, and scientific patterns that support the subjects being taught, 2) Mastery of Competency Standards and Basic Competencies, 3) Development of creativity-enhanced learning materials, and 4) Continuous professional development by taking reflective action yet Optimal because it is in the category of being.